2000
DOI: 10.1126/science.290.5491.481
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Glycerol-Conducting Channel and the Basis for Its Selectivity

Abstract: Membrane channel proteins of the aquaporin family are highly selective for permeation of specific small molecules, with absolute exclusion of ions and charged solutes and without dissipation of the electrochemical potential across the cell membrane. We report the crystal structure of the Escherichia coli glycerol facilitator (GlpF) with its primary permeant substrate glycerol at 2.2 angstrom resolution. Glycerol molecules line up in an amphipathic channel in single file. In the narrow selectivity filter of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
975
1
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 924 publications
(1,020 citation statements)
references
References 39 publications
25
975
1
6
Order By: Relevance
“…Superposition of the backbone traces of the three AQP1 models, coloured in yellow (1FQY), magenta (1IH5) and green (our re¢ned model). 1FX8 denotes the PDB code of the X-ray structure of GlpF [3], 1FQY and 1IH5 the two AQP1 models [1,2], and re¢ denotes our re¢ned AQP1 structure. 1FX8 denotes the PDB code of the X-ray structure of GlpF [3], 1FQY and 1IH5 the two AQP1 models [1,2], and re¢ denotes our re¢ned AQP1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…Superposition of the backbone traces of the three AQP1 models, coloured in yellow (1FQY), magenta (1IH5) and green (our re¢ned model). 1FX8 denotes the PDB code of the X-ray structure of GlpF [3], 1FQY and 1IH5 the two AQP1 models [1,2], and re¢ denotes our re¢ned AQP1 structure. 1FX8 denotes the PDB code of the X-ray structure of GlpF [3], 1FQY and 1IH5 the two AQP1 models [1,2], and re¢ denotes our re¢ned AQP1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…In GlpF glycerol is transported through an amphipathic channel. The selectivity filter in this channel is lined by four residues, , which are crucial for the selective transport of glycerol (Fu et al, 2000;Sui et al, 2001). Alignment of several glycerol-transporting MIPs showed that Trp-48 in GlpF is conserved in Fsp1, the glycerol facilitator from Saccharomyces cerevisiae, whereas it is replaced by phenylalanine in mammalian aquaglyceroporins such as AQP3.…”
Section: An Aquaglyceroporin Is Specifically Expressed In the Seed Coatmentioning
confidence: 99%
“…High-resolution atomic structures of prototypes of each category, aquaporin-1 (AQP1) from mammals and the glycerol facilitator (GlpF) from Escherichia coli, have elucidated aspects of the selectivity of these transporters (Fu et al, 2000;Sui et al, 2001). To some extent the glycerol-transporting MIPs, including GlpF, also allow the passage of water (Borgnia and Agre, 2001), hence their designation as aquaglyceroporins.…”
Section: Introductionmentioning
confidence: 99%
“…There is a considerable body of information on AQP protein structure, because, compared to other membrane proteins, the AQPs are relatively easy to isolate and crystallize for structural analysis by x-ray or electron crystallography. High-resolution x-ray crystal structures exist for AQP1 (Sui et al, 2001), the bacterial glycerol-transporter Glpf (Fu et al, 2000), and the major intrinsic protein of lens fiber AQP0 (Harries et al, 2004). AQP1 monomers contain six tilted alpha-helical domains forming a barrel-like structure in which the first and last 3 helices exhibit inverted symmetry (reviewed in Fujiyoshi et al, 2002;Stroud et al, 2003).…”
Section: Introductionmentioning
confidence: 99%